"Daughter" as a positionality and the gendered politics of taking parents into the field. Issue 4 (9th December 2018) - De Silva, Menusha; Gandhi, Kanchan
Abstract : Research on gendered politics of the field has delved into the practices of accompaniment and its implications on research and knowledge production, particularly through the case of researchers' children and partners. In comparison, the tendency to seek assistance from parents is neglected within the scholarship. Drawing on the PhD fieldwork experiences of two researchers in their "native" country, specifically a Sri Lankan researcher conducting fieldwork in Sri Lanka and a North Indian scholar researching in South India, the paper reveals parents' contribution to the research process, in terms of enhancing researcher credibility, facilitating contact‐making and access, and providing emotional and practical care. The discussion illuminates two aspects of parents' involvement in fieldwork: (1) how the unique nature of parent–child relationships shapes the research process at multiple stages, and (2) how the gendered notions of knowledge production result in parents' contributions being typically unacknowledged. The paper emphasises that a researcher's positionality as a daughter shapes her ability to navigate gendered field sites in her "native" country and is implicated in the wider research process. Abstract : This paper will illuminate why researchers take their parents to field sites and how this strategy helps them to negotiate gendered challenges in the field. Despite the benefits of parental accompaniment, parents' roles are frequently underplayed. This invisibility of certain actors' contributions to the research process reveals the gendered politics of knowledge construction.